Global Security : Addressing the Challenges and Opportunities for Research in the Information Age - Géré, Francois; Sharpe, M. (NATO science for peace and security series. Human and societal dynamics ;, 2011)
The approach to research in global security from the perspective of the human sciences presents a number of challenges. NATO and ESF, aware of the importance of this endeavor, have commissioned l'Institut Francais d'Analyse Strategique (IFAS) to organize a number of activities aimed at identifying potential areas for research. This book presents the findings of these investigations. Whilst the human sciences will of course continue their traditional activities and research, the intention is to establish an additional "security oriented sector" for the new generation, to which each di.